Porcine extraintestinal pathogenic Escherichia coli delivers two serine protease autotransporters coordinately optimizing the bloodstream infection - Pan, Xinming; Chen, Rong; Zhang, Yating; Zhu, Yinchu; Zhao, Jin; Yao, Huochun; Ma, Jiale (Frontiers in Cellular and Infection Microbiology, 2023)
Extraintestinal pathogenic Escherichia coli (ExPEC) is one of the leading causes of bloodstream infections in a broad spectrum of birds and mammals, thus poses a great threat to public health, while its underlying mechanism causing sepsis is not fully understood. Here we reported a high virulent ExPEC strain PU-1, which has a robust ability to colonize within host bloodstream, while induced a low level of leukocytic activation. Two serine protease autotransporters of Enterobacteriaceae (SPATEs), VatPU-1 and TshPU-1, were found to play critical roles for the urgent blood infection of strain PU-1. Although the Vat and Tsh homologues have been identified as virulence factors of ExPEC, their contributions to bloodstream infection are still unclear. In this study, VatPU-1 and TshPU-1 were verified to interact with the hemoglobin (a well-known mucin-like glycoprotein in red blood cell), degrade the mucins of host respiratory tract, and cleave the CD43 (a major cell surface component sharing similar O-glycosylated modifications with other glycoprotein expressed on leukocytes), suggesting that these two SPATEs have the common activity to cleave a broad array of mucin-like O-glycoproteins. These cleavages significantly impaired the chemotaxis and transmigration of leukocytes, and then inhibited the activation of diverse immune responses coordinately, especially downregulated the leukocytic and inflammatory activation during bloodstream infection, thus might mediate the evasion of ExPEC from immune clearance of blood leukocytes. Taken together, these two SPATEs play critical roles to cause a heavy bacterial load within bloodstream via immunomodulation of leukocytes, which provides a more comprehensive understanding how ExPEC colonize within host bloodstream and cause severe sepsis.